Forms of Toxic and Trace Metals in Grassland Soils of Galicia, Spain - Cristina López-Mateo; Raúl Marcos-Rodríguez; Florentino Díaz-Rodríguez; Maria Luisa Fernandez-Marcos; Maria Luisa Fernandez-Marcos (Spanish Journal of Soil Science, 2023)
The application of cattle slurry to agricultural soils contributes to the circular economy, while enriching the soil in macro and micronutrients and organic matter. However, this practice can have deleterious environmental effects, by adding toxic metals and other contaminants. The pseudo-total concentrations of nine potentially toxic and trace metals (Fe, Mn, Zn, Cu, Ni, Co, Cr, Cd and Pb) as well as metals extracted by DTPA, Mehlich 3 and 0.01 M CaCl2 were determined in Galician (NW Spain) grassland soils regularly receiving cattle slurry. Four soil depths (0–5, 5–10, 10–20 and 20–40 cm) were sampled and analysed. The pollution condition was assessed by comparing the pseudo-total concentrations with generic reference levels for Galician soils and by using pollution indices. The results indicated the absence of soil pollution by Fe, Ni, Co, Cr and Pb and a situation of no pollution to moderate pollution by Mn, Zn and Cu. Cd was the element most frequently enriched in the studied soils according to the pseudo-total, DTPA and Mehlich-3 concentrations, while the extraction by CaCl2 pointed to no environmental risk. The study supports the lithogenic character of Fe, Ni, Co and Cr, the mixed lithogenic and anthropogenic nature of Mn, Zn and Cu and the anthropogenic origin of Cd in these soils. The latter element can be added by both the application of cattle slurry and inorganic phosphate fertilisers.